2022
DOI: 10.1038/s41598-022-23088-x
|View full text |Cite
|
Sign up to set email alerts
|

Patient's perspective in clinical practice to assess and predict disability in multiple sclerosis

Abstract: The information provided by a person with multiple sclerosis (MS) may anticipate changes in the course of the disease. To explore the role of a set of standardized patient-reported outcomes (PRO) in predicting disability progression in MS an observational study was conducted in two cohorts of 30 and 86 persons with progressive MS (pwPMS) and relapsing MS (pwRMS), respectively. The associations between baseline clinical, biochemical variables and results on MS quality of life scale (MusiQol), Modified Fatigue I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…Differences need to be acknowledged between fatigue, which is a subjective emotion, and fatigability, which is an objective deterioration of cognitive performance during a single cognitive examination session, although the correlation between fatigue and fatigability still remains unexplained [61]. However, in an observational study of 86 RRMS and 33 PMS patients, assessing how patient-reported outcomes (PROs, including: Multiple Sclerosis Quality of Life [MusiQol], Modified Fatigue Impact Scale [MFIS] and Beck Depression Inventory-II [BDI-II]) can predict MS disability progression, no significant correlation between PROs and SDMT was reported [62].…”
Section: Sdmt and Quality Of Life Fatigue Lifestyle And Other Factorsmentioning
confidence: 99%
“…Differences need to be acknowledged between fatigue, which is a subjective emotion, and fatigability, which is an objective deterioration of cognitive performance during a single cognitive examination session, although the correlation between fatigue and fatigability still remains unexplained [61]. However, in an observational study of 86 RRMS and 33 PMS patients, assessing how patient-reported outcomes (PROs, including: Multiple Sclerosis Quality of Life [MusiQol], Modified Fatigue Impact Scale [MFIS] and Beck Depression Inventory-II [BDI-II]) can predict MS disability progression, no significant correlation between PROs and SDMT was reported [62].…”
Section: Sdmt and Quality Of Life Fatigue Lifestyle And Other Factorsmentioning
confidence: 99%